Economic Integration and Local Tax Mimicking - Carolin Holzmann; Axel von Schwerin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper provides empirical evidence for tax mimicking among unicipalities by exploiting a quasi-experiment in the German local fiscal equalization scheme. We show for the metropolitan area FrankfurtRheinMain that, besides neighborhood, the degree of economic integration of municipalities determines the interdependency among their tax policies. As the metropolitan area spreads across municipalities located in the two German federal states, Hesse and Rhineland-Palatinate, we can show that Rhineland-Palatine municipalities statistically significantly respond in their local tax rates to an exogenous change in the Hessian local fiscal equalization scheme. However, we find tax rate interdependency only for Rhineland-Palatine metropolitan municipalities which are arguably strongly economically integrated with Hessian metropolitan municipalities. The results suggest that regional economic integration is a key determinant for tax mimicking.
Keywords: H20; H71; H70; 330